Humidity Sensitivity and Coil Design of a High-Precision Eddy-Current Displacement Sensor - Johan G. Vogel; Vikram Chaturvedi; Stoyan Nihtianov (Proceedings, 2017)
Unlike capacitive displacement sensors, Eddy-Current Displacement Sensors (ECDSs) possess an inherently low sensitivity to environmental conditions, such as the humidity of the ambient air. By elevating the excitation frequency it is possible to mitigate their major limitations regarding stability and resolution, making them of interest for high-precision displacement sensing. However, by increasing the excitation frequency, ECDSs become less immune to environmental conditions, due to the inevitable parasitic capacitance of the sensing coil. In this work, we formulate a requirement for the minimum Self-Resonance Frequency (SRF) of the coil, based on the specified humidity variation and the allowable displacement error. This requirement provides an input for the design of the high-precision ECDS probe.